Studi Komparasi Tentang Mahārah Al-Qirā'ah Antara Siswa Mukim dan Siswa Nonmukim Pondok Pesantren di MTs Ma’arif Al-Huda Salaman Magelang Kelas VIII Tahun Ajaran 2017/2018 - Mur Tasimah; Achmat Taufiq (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This his study aims to determine the differences in mahārah al-qirā'ah skills between mukim and nonmukim students at MTs Ma'arif Al Huda, Salaman, Magelang. The background of this study is the general assumption that mukim students, because they live in a pesantren environment, have an advantage in Arabic text reading skills. The research method used was quantitative with a field research approach. Data collection techniques included written and oral tests, questionnaires, observation, interviews, and documentation, with a sample of 50 students in class VIII consisting of 25 boarding school students and 25 non boarding school students. Data analysis was conducted using independent t-test. The results showed that there was no significant difference between the mahārah al-qirā'ah skills of mukim and nonmukim students. Factors such as teachers‘ learning methods, learning motivation, and educational environment have a greater influence on students’ reading ability. These findings indicate the importance of a holistic approach in the development of Arabic language learning in madrasah.